Ultrasound findings of carpal tunnel syndrome in a hunter syndrome patient. Issue 1 (26th November 2015) - Alkhachroum, Ayham M.; Preston, David C.
ABSTRACT: Introduction : Hunter syndrome (mucopolysaccharidosis II) is a rare genetic disorder. Carpal tunnel syndrome (CTS) is a common finding in these patients. Methods : We report the ultrasound findings in a 40‐year‐old Hunter syndrome patient with severe CTS. Results : Marked abnormalities of the median nerve were present proximal to the carpal tunnel with an unusual area of increased echogenicity between enlarged fascicles separating the area of maximal enlargement and the normal median nerve proximally. Conclusions : This case demonstrated unique ultrasound findings in a Hunter syndrome with CTS. Ultrasound also localized the median nerve lesion in the setting of end‐stage median neuropathy and nonlocalizing electrophysiology. Muscle Nerve 53 : 147–150, 2016